EXPLORING SEXUALITY IN MY POLICEMAN AND CALL ME BY YOUR NAME: A STUDY OF IDENTITY, REPRESENTATION AND DESIRE. - Chandra, Adheena; Lakshmi M, Aiswarya (International Journal of Research -GRANTHAALAYAH, 2024)
This paper examines the complex portrayal of sexuality in Call Me by Your Name (2017) and My Policeman (2022), highlighting the ways in which identity, desire, and societal norms influence the lives of the main characters. These two cinematic explanations of sexuality delve into how identity, desire, and societal expectations shape the experiences of main characters as they struggle to express their lives through love, repression, and the search for authenticity. Set against distinct historical and cultural perspectives—specifically 1980s Italy and 1950s England, both films explore the personal decisions that queer characters make while navigating the emotional depths of love, repression, and their ongoing journey towards authenticity. In examining these two narratives within their context, this study explores the ways in which gender roles are defined or reinforced, how queer desire is either articulated or silenced, and how these characters manoeuvre through restricted social situations. In the end, however, the overall messages of the films are quite similar: they uncover the inner conflict of recognizing or denying one’s own truth and the emotional strain of concealing one’s desires from the world.